Failure analysis of a transmission tower subjected to combined wind and rainfall excitations. (1st May 2019) - Fu, Xing; Li, Hong‐Nan; Wang, Jia
Summary: Many transmission towers have collapsed during severe gales and thunderstorms, and these failures have traditionally been attributed simply to wind loading. This study attempts to reveal the full failure mechanism of tower structures under strong wind excitation considering the rainfall effect. First, the calculation of rain load for a tower‐line system is provided. Then, an uncertainty analytical method for estimating the strength capacity and predicting the failure pattern of transmission towers induced by wind and rain loads is presented. Next, a real collapsed transmission line is considered to establish the finite element model, followed by the determination of the most vulnerable tower, which is then used to perform the uncertainty analysis. The results illustrate that the collapse basic wind speed considering the rainfall effect is smaller than the pure wind condition. In addition, the failure probability of the tower body is the largest, which is consistent with the deterministic method, whereas the most vulnerable tower began to fail from the tower leg in reality, indicating that the initial broken position of the transmission tower may not occur in the location with the largest probability and that the deterministic method is invalid in some cases. Finally, the influence of the wind attack angle and bundle number of transmission conductor is investigated. The most unfavorable wind attack angle is 90°, and the rainfall effect becomes increasingly significant with increases in the bundle number; this relationship should be given particular attention.